Möbius Syndrome with Poland's Anomaly - Sugarman, Gerald I. (1973)
A five-year-old boy with Möbius syndrome, Poland's anomaly, and dextrocardia is described. These malformations have not been previously reported. The propositus had ipsilateral absence of the sternal portion of the pectoralis major muscle associated with acromicria, syndactyly, brachydactyly of the index, middle, ring, and fifth finger, as well as radiological evidence of hypoplasia of the index middle and ring fingers, associated with syndactylia and absent middle phalanges.